(untitled) (Malaysian Journal of Civil Engineering, 2018)
In Malaysia, issues related to occupational health, especially in the construction industry is not commonly discussed, but data in other countries have indicated major problems associated with occupational illness. Health problems due to stress can increase the cost of health and their impact to human, family, society and the nation cannot be neglected. In the past, study on stress at work is not comprehensive especially in the construction industry. Research for the stress at work place should be done more since it will provide vital information toward producing a sustainable human resource that can contribute significantly to our country. The aim of the study is to examine the level and extent of work–related stress and the prevalence of health problem among the contractors’ management team at construction sites. The study is conducted in the district of Johor Bahru. The respondents involved were from contractors’ management teams such as engineers, supervisors and project managers. The number of questionnaire forms sent was 500 sets and only 300 sets were replied by engineers, supervisors and project managers. The questionnaire data were analyzed using frequency analysis method and average index method. The findings showed, about 30 percent of the respondents, a total of 90 respondents, agreed that they underwent and experienced some illness, disability or other physical or mental problems that was triggered or made worse by job or work carried out within the last year. Around 13% of the respondents working in the construction site job roles currently suffered from stress, depression or anxiety which they felt was caused by or made worse by their job or work carried out in the past. Around 7% of the respondents found their job extremely stressful especially when they had to be responsible for the safety of others at work. Other sources of stress were related to time constraint and lack of resources.